Bikel SIN-KB: Solusi Efektif untuk Meningkatkan Keterampilan Reflektif Guru dan Kepala Sekolah dalam Pembelajaran - Murtadlo, M. Ali; Tiyas, Nenin Maining (KAMBOTI: Jurnal Sosial dan Humaniora, 2025)
This study investigates the impact of the Bikel SIN-KB program on improving the reflective practices of teachers and school principals in primary schools, focusing on enhancing teaching quality and student outcomes through the development of learning communities and the application of the Inquiry Cycle in Community Learning. Conducted in 18 primary schools in Mojowarno, Jombang, Indonesia, the research used a qualitative approach with action research methodology, consisting of four stages: planning, action, observation, and reflection. Data collected through interviews, observations, and document analysis revealed significant improvements in teachers' and principals' skills in developing learning communities and applying reflective practices. The implementation of the Inquiry Cycle fostered collaboration and problem-solving among educators, which ultimately led to better teaching practices and student achievement. The study also emphasized the need for continuous professional development tailored to the specific needs of each school and classroom. The findings suggest that the Bikel SIN-KB program effectively supports reflective teaching practices and collaboration, contributing to enhanced educational practices. Future research should consider expanding the scope to include more schools and examine the long-term impact of reflective practices on student performance.